Analysis of the budgetary execution of the city of São Paulo (2002-2019) from the perspective of the scored equilibrium theory - Silva, Maurício Correa da (2021)
This investigation aims to analyze whether decision making in budgetary executions in the municipality of São Paulo, from 2002 to 2019, was carried out based on incremental processes (stability) or scored with the support of the Punctuated Equilibrium Theory (PET). The analyzes were performed with updated data for March 31, 2020. The Kolmogorov-Smirnov and Shapiro-Wilk tests were used to test the normality or otherwise of variations in budgetary executions. The results showed that decision making in budgetary executions in the municipality of São Paulo of total revenue and expenditure occurred based on incremental processes (stability). The execution of expenses by government functions (Legislative, Judiciary, Administration, Education, Health, etc.) occurred based on punctuated (atypical) processes. The study corroborates the use of the support of the Punctuated Equilibrium Theory (PET) in the analysis of budgetary policy in Brazilian municipalities. It is concluded that the budgets of the Municipality of São Paulo are prepared incrementally, but their executions have a pattern of stability with interruptions (scores). The research contributes to the advancement of literature in the analysis of the execution of budgetary policy in a theoretical and practical way. The methodological approach may be used by other researchers as guidance and encouragement for other similar research. It can be said that, from a social point of view, the results of this investigation can be used by budget policy makers and as a way of reducing information asymmetries about budget management for citizens.